The nonbank footprint of banks - Nicola Cetorelli; Saketh Prazad (Federal Reserve Bank of New York, 2024)
U.S. bank holding companies (BHCs) have developed a very significant nonbank footprint over the years, adding thousands of specialty lenders, brokers and dealers, asset management, and insurance subsidiaries to their organizations. These nonbank subsidiaries represent a sizeable share of aggregate BHC assets and a significant component of the entire U.S. nonbank industry. We argue that liquidity management synergies are an important driver of the coexistence of commercial banks and nonbank subsidiaries within BHCs. Using unique data on BHC organizational structure and financial reports, we show that in the unrestricted pre-crisis regulatory environment, commercial banks within BHCs with a large nonbank footprint hold fewer liquid assets and more loans on their balance sheet. We show that our results are driven by explicit and implicit intracompany funding arrangements between affiliated banks and nonbanks. Post-GFC banking regulation, like resolution planning and liquidity regulation, has disrupted liquidity synergies and has caused BHCs to scale back their nonbank footprint.
Keywords: G01; G21; G23; G28; 330; banking firm; bank holding companies; firm boundaries; nonbank financial institutions; liquidity synergies; bank regulation